PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 027 SINTONG KECAMATAN TANAH PUTIH - Mirawati Mirawati; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract. Back Background problem in research this is its low of result study class student IPS IV Country SD 027 Sintong with value average 65. From 16 student that yet finish many 9 people (43,75%) whereas who finish 7 people (56,25%). problem Rumusam in this research what implement the Cooperative Studying model TPS's Type ( Think Pair Share) can to level it result study the IV SD class Country 027 Sintong?. data collection Instrument to this penelitiaan is sheet the Research is done dalan two cycles, that is four times material meeting two times repeating of daily. data collection Instrument to this penelitiaan is teacher's observation sheet and student also result test study. After to be applied model Cooperative studying TPS's Type ( Think Pair Share) so research result show that activity of teacher to cycle first meetings first be obtained persentase 58,33% with enough category, to meeting second cycles first 66,66% with good category, first cycles meeting second 75% good categoryy, second cycles meeting second 87,5% categoryy very good. To cycle first meetings first persentase activity of student 54,16% enough categoryy, second cycles meeting first persentase activity of student 62,5% good categoryy, first cycles meeting second with persentase 66,66% good categoryy, second cycles meeting second with persentase 83,33% categoryy very good. To student's skor base who finish 7 people whereas that don't finish 9 people, with classical completing 43,75% (don't finish). To cycle daily repeating first, student who finish 11 people whereas that don't finish 5 people, with classical completing 68,75% (don't finish). To cycle end repeating second to undergo leveling of completing, student who finish 15 people and that don't finish 1 people, with completing classical 93,75% (finish). this research result To be based can to be concluded that the Cooperative studying model-implement TPS's Type ( Think Pair Share) can to level it result study class student IPS IV Country SD 027 Sintong. From research that had be done to be suggested to the other examiner that the Cooperative studying model TPS's Type ( Think Pair Share) can be made reference or base to to be applied to the the other lesson eye so that its reacher studying result that better more.Key Word: The Cooperative Studying Model TPS's Type (Think Pair Share),Result study IPS